Analysis of Pedestrian During The COVID – 19 Period in The Dago – Bandung Area - Muhammad Isradi; Nofila Sari; Amar Mufhidin; Widodo Budi Dermawan; Mohammad Khadem (Journal of World Conference (JWC), 2022)
The sidewalk in the Dago - Bandung area is one of the sidewalks that is widely used by pedestrians because there are schools, campuses, hospitals, clothing stores and restaurant. This study to determine the average daily use of sidewalks in the Dago - Bandung area, identify sidewalk facilities, determine level of services sidewalks, and obtain pedestrian perceptions of sidewalk facilities. This study used the field survey to primary data and quisioner from pedestrians for secondary data. Analysis of sidewalk facilities uses the Regulation of the Minister of Public Works Number 3 of 2014 while level of service uses High Capacity Manual method. Pedestrian perceptions use the Importance Performance Analysis method. The survey showed on the largest pedestrian volume occurred on Sunday at 2.49 people/minute and it was found that the sidewalks in the Dago - Bandung area had met standards. Based on the results the level of service on the sidewalk is Standard A with the average pedestrian flow of 1.64 ppl/m/mnt and the average space for pedestrians of 34.62 m2/ppl. The results of the Cartesian diagram obtained in quadrant I. The main priority is the condition of the signage, the location of the street furniture, and the cleanliness of the channel. Overall, a few items need improvement in order to create better comfort for pedestrians.